1981
DOI: 10.1111/j.1432-1033.1981.tb05631.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Higher-Order Structure of Chicken-Erythrocyte Chromatin in Solution

Abstract: A detailed hydrodynamic study of chicken erythrocyte chromatin as a function of ionic strength, and comparison with results reported earlier for rat liver chromatin [Butler, P. J. G. and Thomas, J. 0. (1980) J . Mol. Bid. 140,529; Thomas, J. 0. and Butler, P. J. G. (1980) J . Mol. Biol. 144,[89][90][91][92][93] shows similar behaviour in the two cases, but quantitative differences indicate a greater stability of the chicken erythrocyte chromatin. The hydrodynamic method may thus provide a general assay for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(69 citation statements)
references
References 31 publications
(34 reference statements)
5
63
0
Order By: Relevance
“…This suggests that some new state of compaction is possible with the larger polynucleosomes, consistent, for example, with the completion of one turn of a simple superhelix or solenoid. Similar sedimentation results were obtained with chicken erythrocyte chromatin (2) . In an attempt to understand this effect, we have examined the structure of tetra-to heptanucleosomes in different NaCl concentrations using the micareplica technique.…”
Section: Compatibility With Other Measurementssupporting
confidence: 85%
“…This suggests that some new state of compaction is possible with the larger polynucleosomes, consistent, for example, with the completion of one turn of a simple superhelix or solenoid. Similar sedimentation results were obtained with chicken erythrocyte chromatin (2) . In an attempt to understand this effect, we have examined the structure of tetra-to heptanucleosomes in different NaCl concentrations using the micareplica technique.…”
Section: Compatibility With Other Measurementssupporting
confidence: 85%
“…In these respects the neuronal chromatin was similar in appearance to erythrocyte higher order fibers (Fig. 7, b and c), (6,24), and to the fibers that have been described for other chromatins under similar conditions (36). Chromatin that had been prepared by reconstitution of depleted neuronal polynucleosomes with calf thymus H 1 presented similar structures to those seen in the native samples (Fig.…”
Section: Electron Microscopysupporting
confidence: 75%
“…Previous work has revealed that H 1 is located on a nucleosome, or chromatosome (33), at that point where the DNA both leaves and enters the nucleosome (2,6,33) . The characteristic protection from nucleases of a DNA fragment 168 base pairs long occurs as a direct result of this interaction (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin was prepared as described in ref. 26. Briefly, nucleosomes were isolated by solubilizing chromatin from purified chicken erythrocyte nuclei with micrococcal nuclease.…”
mentioning
confidence: 99%